Optimizing Electric Vehicle Operations for a Smart Environment: A Comprehensive Review - Mehrdad Tarafdar-Hagh; Kamran Taghizad-Tavana; Mohsen Ghanbari-Ghalehjoughi; Sayyad Nojavan; Parisa Jafari; Amin Mohammadpour Shotorbani (Energies, 2023)
The transportation sector is one of the main contributors to the emission of greenhouse gases globally, and the electrification of this sector can significantly reduce the emission of pollutants. The widespread connection of electric vehicles (EVs) to the power grid may bring challenges, such as increasing the peak load of the network. Therefore, the optimal use of EVs is necessary to improve the network’s economic, security, and stability indicators. This review article examines the deterministic control model and centralized control model, the types of EV models, and their tabular comparison. Additionally, expressing the communication standards to deal with compatibility challenges in charging stations, the effects of EV integration with the power grid, and various methods such as smart charging, dumb charging, and flexible charging are the main goals of this review article. In addition, since batteries play a crucial role in the electric vehicle industry, this research investigates the oldest type of rechargeable battery to the latest battery technology and the energy management system of these batteries. Finally, the authors have conducted studies on government incentives, the adverse effects of these incentives, and the combination of EVs with renewable energy sources.